International trade brings sustainability to Central Asia (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
The growing demand for organic and fair traded commodities on the world market provides producers and buyers opportunities to strengthen their relation and improve sustainability in the value chain. What are the challenges of building an international supply chain to foster local economic development?